Effectiveness of Stress Management Training on Hope and Interpersonal Compatibility of Addicts under Treatment - Z Sepehrinasab; F Hossein Sabet (Drug Control Headquarters, Research and Education Office, 2016)
Objective: The current study was aimed to examine the effectiveness of stress management with behavioral–cognitive mode in the promotion of hope and socio-affective adjustment of drug abusers under methadone maintenance treatment. Method: A quasi – experimental research design, along with pretest-posttest and control group was employed for the conduct of this study. In this regard, the number of 20 drug abusers under methadone maintenance treatment was selected by convenience sampling method and these participants were assigned into experimental group (10 individuals) and control group (10 individuals). The participants received ten training sessions and, then, completed Snyder's Trait Hope Scale and Bell’s social adjustment scale (BAS). Results: The results of the study showed that there is a significant difference between the two groups in terms of hope and affective and social adjustment. In fact, the experimental group experienced a considerable promotion. Conclusion: It can be concluded that stress management with behavioral–cognitive training can be an effective interventionist method for the addicts under methadone maintenance treatment.